Establishing an irrigation performance index the case of Angat-Maasim Rivers Irrigation System - Caluag, Rauf Micko A.
The researcher finds it important to devise an irrigation performance index that would depict the overall performance of the irrigation system by incorporating a number of performance indicators. In this study, average yield in cavans per hectare, ratio of irrigated area over service area, water diverted to canals over irrigation diversion requirement, collection efficiency, and financial viability were utilized in formulating an index. These indicators were chosen because they correspond to the general objectives of an irrigation scheme which are as follows: production, rational utilization of resource, equity, profitability, and sustainability. Weights assigned for the five performance indicators were 35%, 25%, 15%, 10%, and 15% respectively, based what matters more with regards to the objectives and intended functions of the managing group. Five performance levels made up the irrigation performance index: poor, bad, fair, good, and excellent. Each level was assigned with a rating of 1, 2, 3, 4, and 5 respectively, 5 being the highest. The index was then used in the case of AMRIS from 2000 up to 2012. It was shown that the overall performance rating of AMRIS during dry season based from the devised index varied from 2.65 up to 4.05, from almost a fair performance to a good perfonnance. On the other hand, during wet season, overall performance ratings were a little lower, ranging from 1.9 up to 3.8. Recommendations on how to further improve the study and how to utilize the devised irrigation performance index were made after.